Automotive Technology: A Systems Approach - Erjavec Jack (Thomson Learning, 2005)
The leading authority on service and repair procedures for contemporary automobiles remains the most technically comprehensive on the market! The fourth edition of Automotive Technology: A Systems Approach has been updated to reflect the most recent technological developments in the industry and features state-of-the-art coverage of hybrid vehicles, GPS systems, electronic ignition systems, DIS, fuel injection systems, and more. This enhanced presentation of the theory, diagnosis, and service of automobiles and light trucks takes into account all the latest trends, including variable valve timing, lift and variable compression ratios, fuels and alternative energy sources, as well as the latest engine designs and technologies. The "must have" information contained in this book will help readers understand and efficiently diagnose and service yesterday's, today's, and tomorrow's automotive systems and vehicles.